2017
DOI: 10.1111/1749-4877.12242
|View full text |Cite
|
Sign up to set email alerts
|

Cultivated walnut trees showed earlier but not final advantage over its wild relatives in competing for seed dispersers

Abstract: Little is known about seeding regeneration of cultivated trees compared to wild relatives in areas where seed dispersers are shared. Here, we investigated the differences in seed fates of cultivated walnut (Juglans regia) and wild Manchurian walnut (Juglans mandshurica) trees under rodent predation and dispersal. J. regia seeds have higher nutritional value (large size, mass and kernel mass) and lower mechanical defensiveness (thin endocarp) than J. mandshurica seeds. We tracked seeds of J. regia and J. mandsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 38 publications
0
13
1
Order By: Relevance
“…Seed fate is critical for achieving plant population regeneration during seed dispersal (Vander Wall 2001;Jansen et al 2004;Zhang et al 2017). In general, the more seeds that are scatter-hoarded by seed hoarders, the better the seed germination and the establishment of seedlings are (Wang et al 2014;Zhang et al 2016a).…”
Section: Discussionmentioning
confidence: 99%
“…Seed fate is critical for achieving plant population regeneration during seed dispersal (Vander Wall 2001;Jansen et al 2004;Zhang et al 2017). In general, the more seeds that are scatter-hoarded by seed hoarders, the better the seed germination and the establishment of seedlings are (Wang et al 2014;Zhang et al 2016a).…”
Section: Discussionmentioning
confidence: 99%
“…Granivorous rodents are important seed predators and are ubiquitous in almost every ecosystem (Moles et al 2003;Zhang et al 2017;Dittel & Vander Wall 2018). Many studies have examined density-dependent effects on post-dispersal seed predation by rodents, but the results of these studies remain controversial, as studies have shown positive (Baraibar et al 2012;Pardini et al 2017) and negative density-dependent patterns (Romo et al 2004;Daedlow et al 2014) and density-independent results (Lott et al 1995;von Allmen et al 2004;Haught & Myster 2008;Rosin & Poulsen 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The dispersal and establishment of seeds are regarded as one of the most vulnerable and limiting stages in the plant life cycle (Chen, Tomlinson, Cao, & Wang, ; Janzen, ; Zhang, Chu, & Zhang, 2017a; Urgoiti, Muñoz, Espelta, & Bonal, ). Successful seed survival and seedling establishment are often threatened by a variety of biotic and abiotic factors (Bogdziewicz et al, ; Canelo, Gaytán, Gonzálezbornay, & Bonal, ; Gómez, Puerta‐Piñero, & Schupp, ; Hou, Yi, Yang, & Liu, ; Wallertz & Petersson, ; Zhang, Wang, Liu, & Yi, 2017b).…”
Section: Introductionmentioning
confidence: 99%